How to Align Management Commitments to the Successful Implementation of Management Accounting Information Systems in Manager Decision Making - Lesi Hertati; Otniel Safkaur; Aoron M. Simanjuntak (Yayasan Ilomata, 2020)
This study investigates the effect of management commitment on the successful application of management accounting information systems and their implications for manager decision making. The unit of analysis in this study is the functional unit in Small and Medium Enterprises in Indonesia. This research also implies that the responsiveness of organizations to the successful implementation of management accounting information systems is very important not only for internal and external but for the organization itself in building a sustainable corporate image, and successes that enhance organizational reputation and manager's understanding of financial and non-financial information. finance is in line with the increasing commitment of the management in the company. Furthermore, this study states that management commitment influences the success of management accounting information systems and their implications for manager decision making. The Lisrel SEM modeling results confirm that management's commitment to the success of management accounting information systems and their implications for managerial decision making have a significant effect.